The Significance of Dreams in the New Testament - Zikri, Khairullah (Religi: Jurnal Studi Agama-agama, 2002)
This article intends to highlight that the New Testament regards dreams as one significant way in which God chooses to reveal himself. Since the central message of the new testament is that God has uniquely revealed himself in Christ, dreams are always seen as secondary to this central revelation and are significant only in relation to God's revelation in Jesus. It is in this way that the scarcity of dreams reports in this book might be understood. With the coming of Jesus Christ, is dream fade in importance since he is the new revelation of God. It is now the risen Jesus who speaks, therefore the particular mode of revelation is really unimportant.